The outcomes of childhood acute lymphoblastic leukemia with hyperleukocytosis - Din Alfina; Pudjo Hagung Widjajanto; Suryono Yudha Patria (Paediatrica Indonesiana, 2018)
Background Hyperleukocytosis in childhood acute lymphoblastic leukemia (ALL) is an emergency in oncology. This condition showed high mortality and relapse rates, as well as low survival rate. The outcomes of this group of patients are not yet well studied. Objective To evaluate the characteristics and outcomes of childhood acute lymphoblastic leukemia (ALL) with hyperleukocytosis. Methods This was a retrospective cohort study. The patients were children less than 18 year of age who were diagnosed as ALL in Dr. Sardjito Hospital, Yogyakarta, from January 1st 2010 to November, 30th 2016. Event-free survival rate and overall survival rate were estimated for group of patients with the white blood cell (WBC) groups 50-200x109/L and >200x109/L using the Kaplan-Meier method. Results There were 705 children diagnosed as ALL during the study period, 129 (18%) with hyperleukocytosis and 111 of them met the inclusion criteria, consisted of 76 children in a group of WBC 50-200 x 109/L and 35 children in a group of WBC >200 x 109/L. Presentation at diagnosis: median age were 7 years (range 1 month-18 years), male was 1.5 higher than female, 92% of cases with lymphoid infiltration, 5% with CNS involvement, 40% had bleeding tendency, and 10% had clinical tumor lysis syndrome (TLS). Median WBC was 122 (range 53.4-876) x 109/L; mean Hb was 8 (SD 3) g/dL; median platelet count was 30 (range 1-221) x 109/L. Immunophenotyping was done in 23 patients, 5/23 (8%) was T cell. The patients in lower WBC group showed lower death (26% vs. 34%, P=0,389), higher two-year event-free survival (EFS) 68% vs. 45%, P=0.003, and overall survival (77% vs. 68%, P= 0.16), compared to patients in higher WBC group. Univariate and multivariate Cox regression analyses revealed that none of the variables was a significant prognostic factor for 2 years EFS or overall survival. Conclusion The group of children with ALL and hyperleukocytosis with lower WBC at diagnoses showed better outcomes than the higher WBC.